Utilization and comparison of family planning services through national family health survey in Uttarakhand, India - Singh, Ankit; Khan, Firoz; Gaur, Ashish (International Journal of Research in Medical Sciences, 2019)
Background: India was the first country to start family planning program in 1952. In the first 50 years there have been many changes in India. The family planning program name was changed from time to time. At the present scenario, its name is Reproductive and Child Health. In this study, authors evaluate utilization of family planning services with an objective to compare distribution of family planning services between the two regions of Uttarakhand: Garhwal and Kumaon. Methods: In this study, data mining was done using secondary database with the permission from International Institute for Population Sciences (IIPS) NFHS-4 data to carried out during 2015-2016 in Uttarakhand, India and estimate of the values for all the parameters of Family Planning was estimated. A statistical Z-score test was performed in the estimated of proportions in all study parameters of the family planning. Results: The study indicates that between the two divisions Garhwal has more utilization of family planning services as comparatively higher than Kumaon. Pithoragarh from the Kumaon division has more utilization proportion of family planning services in comparison to the other districts in the division, while Almora were recorded as the minimum use of family planning services. Uttarkashi in Garhwal region accounted for major proportion of utilization of family planning services, while Haridwar had minor proportions. Conclusions: Though overall utilization of family planning services of Uttarakhand is far better than other states in India but between the two divisions, Kumaon requires more attention in terms of utilizing services and awareness programmes. In fact, certain districts in Garhwal also require intervention from the Government to improve health quality. Both hilly and urban districts have different issues, which needs to be targeted to improve the health quality of the state.